The Effect of Providing Oodev (OOcyte Developer) with Different Doses on Gonad Maturity and Egg Hatching of Baung Fish (Hemibagrus nemurus) - Inda Feriwanti Silitonga; Nuraini Nuraini; Sukendi Sukendi (Jurnal Akuakultur SEBATIN, 2022)
The aim of this research was to determine the effect of oodev on gonad maturation of Baung (Hemibagrus nemurus). This research was conducted from February 2020 – February 2021 at Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine Faculty University of Riau. Data analyzed descriptively, the method used is an experimental with four treatments anf three replications. The treatment were P0 (Oodev 0 ml/kg body weight), P1 (Oodev 0,3 ml/kg body weight), P2 (Oodev 0,5 ml/kg body weight), and P3 (Oodev 0,7 ml/kg body weight). The result showed that Oodev on gonad maturation of P1 (Oodev 0,3 ml/kg body weight) was number off eggs stripping 196 egg/g broodstock, increase of diameter belly 16,93 cm, ovisomatic index 16,87%, fertilization rate 69,77%, hatching rate 76,42 % and survival rate 80%. The water quality parameters obtained temperature 27-310C, pH 5-6, and dissolved oxygen 5-7 ppm.